Perfect betrayal by Season Vining - Vining,Season (2015)
To the outside world, Taylor Hudson has it all: money, beauty and social status. But Taylor's privileged life is far lonelier than it appears. Now it's about to be rocked to its core when a gorgeous new employee shows up at her family's mansion...but nothing about him is what it appears.